Influence of School Environmental Factors on Teaching and Learning Process in Public Primary Schools: A Case of Bungoma County, Kenya - Ochwada , E. Y.; Oseko , A.; Murunga , F. (African Journal of Education,Science and Technology (AJEST), 2019)
School environment affects the teaching-learning process. This paper presents the findings of a study undertaken to investigate the influence of school environmental factors on the teaching-learning process in public primary schools in Bungoma south sub-county, Bungoma County, Kenya. A descriptive survey research design was used. The target population was the Head Teachers/deputy head teachers, Class Teachers, and Pupils in the Public Primary Schools in Bungoma south Sub-county, Bungoma County. Stratified sampling, Simple random sampling and Purposive sampling were used. A sample size of 30 % of the target population was used. Primary data was collected using Questionnaires and Focus group discussions. Data was analysed using statistical package for social sciences (SPSS). Results of this study showed that sufficiency of physical facilities specifically adequacy of classrooms significantly affect the teaching-learning process. Those who reported having adequate classrooms performed better than those who reported inadequacy (Z=1.776, 0.046). Sufficiency of instructional materials, Class size, and School location does not significantly affect the process of teaching and learning. The study concluded that among the school environmental factors, physical facilities particularly adequacy of classrooms, was the only factor that significantly affected teaching and learning and therefore recommends that National and County governments should ensure that classrooms are adequate in Public primary schools.